Small intestinal ulceration secondary to carcinoid tumour arising in a Meckel's diverticulum. Issue 1 (1st January 1999) - McCluggage, W G; McConnell, L; Sloan, J M; Ellis, P K; Irwin, S T
Abstract : A solitary small intestinal ulcer associated with a carcinoid tumour in a nearby Meckel's diverticulum was found in a 77 year old man presenting with massive rectal bleeding. Angiography and a radioisotope study localised the bleeding to the ileum. At operation, the Meckel's diverticulum was identified, with bleeding from an ulcer just distal to it. Pathological examination revealed a small carcinoid tumour confined to the Meckel's diverticulum. Close to the opening of the diverticulum, within the ileum, a well demarcated ulcer was present. Histology showed a non-specific ulcer which eroded a large blood vessel. This is the first documented occurrence of solitary small intestinal ulceration in association with a carcinoid tumour. Carcinoid tumour should be added to the list of possible causes of small intestinal ulceration. The ulceration may be secondary to release of cytokines by the tumour.